p53 Negatively Regulates the PR55\(α\) Subunit of PP2A Ser/Thr Phosphatase Via FBXL20-mediated Proteasomal Degradation - Lepakshe S.V. Madduri; Alison L. Camero; Keith R. Johnson; Michel M. Ouellette; Ying Yan (Achievements and Challenges of Medicine and Medical Science Vol. 3, 2024)
Protein Phosphatase 2A (PP2A) is a family of holoenzyme complexes, which constitute the major Ser/Thr phosphatase activities in human cells. Each PP2A complex consists of one catalytic subunit, one scaffold subunit, and a regulatory subunit. The latter determines the substrate specificity of the PP2A complex. PR55\(α\) is one of PP2A’s 27 possible regulatory subunits. Previous studies by us and others have defined an important role for PR55\(α\) in the support of critical oncogenic pathways required for tumorigenesis and the malignant phenotype of pancreatic cancer. Our studies subsequently reveal a novel function of the p53 tumor suppressor in inhibiting the protein stability of PR55\(α\) via FBXL20, a p53-target gene that serves as a substrate recognition subunit for the SCF (Skp1_Cullin1_F-box) E3 ubiquitin ligase complex. HPNE-E6, HPNE-E7, and HPNE-E6/E7 cell lines were established by transducing HPNE cells with retroviral vectors expressing the E6 and/or E7 proteins of the HPV 16 virus. All antibodies were purchased from Cell Signaling Technology (Danvers, MA) unless otherwise indicated. Immunoblotting (IB) and immunoprecipitation (IP) were performed. Immunofluorescence and microscopy were also performed. For statistical analysis, Student’s t-test and one-way ANOVA methods were used for the comparison of experimental groups using SigmaPlot software. The results show that inactivation of p53 by siRNA-knockdown, gene-deletion, HPV/E6-mediated degradation, or expression of the loss-of-function mutant p53R175H results in increased PR55\(α\) protein stability, accompanied by reduced protein expression of FBXL20 and decreased ubiquitination of PR55\(α\). Likewise, knockdown of FBXL20 by siRNA mimics p53 deficiency, reducing PR55\(α\) ubiquitination and increasing PR55\(α\) protein stability. Functional tests indicate that p53R175H or PR55\(α\) overexpression results in an increase of c-Myc protein stability with concomitant dephosphorylation of c-Myc-T58, which is a PR55\(α\) substrate, whose phosphorylation otherwise promotes c-Myc degradation. A significant increase in anchorage-independent proliferation is also observed in normal human pancreatic cells expressing p53R175H or, to a greater extent, overexpressing PR55\(α\). Consistent with the frequent loss of p53 function in pancreatic cancer, FBXL20 mRNA expression is significantly lower in pancreatic cancer tissues compared to pancreatic normal tissues and low FBXL20 levels correlate with poor patient survival. In summary, this chapter delineates an important new mechanism by which the p53/FBXL20 axis negatively regulates PR55\(α\) protein stability as a part of p53’s tumor suppression function.